INTENSITAS MENGAKSES POSTINGAN SAVE PALESTINA DI MEDIA SOSIAL TERHADAP PERILAKU IBU RUMAH TANGGA DALAM GERAKAN BOIKOT PRODUK ISRAEL - Wahdiyana, Fika; Muslikhah, Febri Palupi; Ernawati, Erna (Fakultas Ilmu Dakwah dan Komunikasi, 2025)
The Israeli-Palestinian conflict is one of the conflicts in the Middle East. So far no conflict has ended and no meeting has been found. This research aims to analyze the impact of the concentration of